Photocatalytic and Greenes Analysis of Magnetic Biochar prepared from Banana (Musa acuminata) Peel Waste - Tri Rizky, Indah; Nurlaela, Nunung; Kamari, Azlan; Sagadevan, Suresh; Fatimah, Prof. Dr. Is (Chemistry Department, Universitas Islam Indonesia, 2026)
In this research, magnetic biochar was prepared from Kepok (Musa acuminata) banana peel. The prepared material was developed as photocatalyst for rhodamine B degradation in aqueous solution. The synthesis was performed via impregnation of iron precursor followed by pyrolysis at 600oC for 2h. Characterization of prepared material was performed using XRD, FTIR and VSM. The instrumental analysis revealed the formation of dispersed iron oxide in the carbonaceous structure of the biochar with magnetism of 1.91 emu g⁻¹. The material showed highly photoactive towards Rhodamine-B degradation with an optimum efficiency of 98.85%. Analysis of the greenness of material preparation was measured using GREEnness Metric (AGREE) and it is reported that a score of 0.73, indicating good compliance with the principles of green chemistry. These results prove that banana peel-based magnetic biochar has the potential as an environmentally friendly material for dye wastewater treatment.